Transitioning across professional boundaries in midwifery models of care: A literature review. Issue 3 (June 2019) - Baldwin, Adele; Harvey, Clare; Willis, Eileen; Ferguson, Bridget; Capper, Tanya
Abstract: Background: High-risk pregnancy, or one with escalating complexities, requires the inclusion of numerous health professions in care provision. A strategy of midwife navigators to facilitate the smooth transition across models of care and service providers has now been in place in Queensland, Australia, for over twelve months, and a formal review process will soon begin. Navigators are experienced nurses or midwives who have the expertise and authority to support childbearing women with chronic or complex problems through the health system so that it is co-ordinated and they can transition to self-care. This includes ensuring a logical sequence in tests and procedures, providing education, or facilitating access to specialist care. The navigator evaluation included a review of existing models of care that support women with chronic and complex needs during their pregnancy. This paper describes the integrative literature review that explored the transitioning of care models. Methods: The review followed formal Preferred Reporting Items for Systematic Reviews and Meta-analyses guidelines, utilised the Critical Appraisal Skills Program tools and analysed a final 33 papers, published from 2000 onwards in professional, peer-reviewed journals and databases. Results/Conclusions: Four key themes of communication, context, visibility and frames were identified, discussed in depth, and considered in the current body of knowledge. The outcomes refer clearly to 'property rights' or turf protected by invisible fences and gatekeeping by midwives and other health professionals. This review may inform development of future frameworks and practice review to better address the needs of pregnant women.